2003
DOI: 10.1517/13543784.12.5.853
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed and its emerging role in the treatment of thoracic malignancies

Abstract: Pemetrexed (Alimta); Eli Lilly and Co., Indianapolis, IN, USA) is a unique multitargeted antifolate that inhibits at least three enzymes, thymidylate synthase, dihydrofolate reductase and glycinamide ribonucleotide formyltransferase. This novel drug is being evaluated in a comprehensive clinical programme for use in both front-line and second-line therapies. It has shown broad activity in a number of solid tumours, including colon cancer, breast cancer, lung cancer, head and neck, cervical cancer and others. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This agent acts by inhibiting at least three intracellular enzymes (thymidine synthase, dihydrofolate reductase, glycinamide ribonucleotide formyltransferase) that are essential for DNA and RNA synthesis [84]. Following phase II studies of pemetrexed that demonstrated promising activity in advanced NSCLC [85], a phase III trial was conducted to compare the efficacy of pemetrexed to docetaxel for advanced NSCLC patients who progressed with one prior chemotherapy regimen [86]. The trial was designed to show non-inferiority for pemetrexed.…”
Section: Salvage Treatment Options For Advanced Nsclcmentioning
confidence: 99%
“…This agent acts by inhibiting at least three intracellular enzymes (thymidine synthase, dihydrofolate reductase, glycinamide ribonucleotide formyltransferase) that are essential for DNA and RNA synthesis [84]. Following phase II studies of pemetrexed that demonstrated promising activity in advanced NSCLC [85], a phase III trial was conducted to compare the efficacy of pemetrexed to docetaxel for advanced NSCLC patients who progressed with one prior chemotherapy regimen [86]. The trial was designed to show non-inferiority for pemetrexed.…”
Section: Salvage Treatment Options For Advanced Nsclcmentioning
confidence: 99%